2023
DOI: 10.1002/moda.1
|View full text |Cite
|
Sign up to set email alerts
|

Why cutting respiratory CO2 loss from crops is possible, practicable, and prudential

Abstract: Plants release back to the atmosphere about half of the CO2 they capture by photosynthesis. Decreasing the rate of crop respiration could therefore potentially increase yields, store more carbon in the soil and draw down atmospheric CO2. However, decreasing respiration rate has had very little research effort compared to increasing photosynthesis, the historically dominant metabolic paradigm for crop improvement. Conceptual and technical advances, particularly in protein turnover and directed enzyme evolution,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 85 publications
0
5
0
Order By: Relevance
“…There is also evidence that eCO 2 directly stimulate maize leaf photosynthesis by reducing the time needed for stomatal opening under dynamic irradiance ( Leakey et al., 2005 ), decreasing stomatal aperture ( Ainsworth and Rogers, 2007 ), increasing intercellular CO 2 concentration (C i ) and leaf temperature, and altering diurnal CO 2 fixation patterns ( Ghannoum et al., 2000 ), resulting in increased photosynthesis. Decreasing respiration has been a target for improving photosynthesis ( Joshi et al., 2023 ), early studies attributed eCO 2 enhanced photosynthesis of immature fully exposed leaves to suppressed photorespiration and enhanced energy use efficiency from decreased leakage of CO 2 from bundle sheath cells and reduced over-cycling of the C4 pump ( Cousins et al., 2001 ; Ainsworth and Rogers, 2007 ). A more recent study showed that eCO 2 led to an 8.4% reduction in day respiration rate and a 16.2% reduction in dark respiration, as decreased leaf N and chlorophyll contents ( Sun et al., 2022 ).…”
Section: Securing Reproductive Success By Harnessing Co 2 ...mentioning
confidence: 99%
“…There is also evidence that eCO 2 directly stimulate maize leaf photosynthesis by reducing the time needed for stomatal opening under dynamic irradiance ( Leakey et al., 2005 ), decreasing stomatal aperture ( Ainsworth and Rogers, 2007 ), increasing intercellular CO 2 concentration (C i ) and leaf temperature, and altering diurnal CO 2 fixation patterns ( Ghannoum et al., 2000 ), resulting in increased photosynthesis. Decreasing respiration has been a target for improving photosynthesis ( Joshi et al., 2023 ), early studies attributed eCO 2 enhanced photosynthesis of immature fully exposed leaves to suppressed photorespiration and enhanced energy use efficiency from decreased leakage of CO 2 from bundle sheath cells and reduced over-cycling of the C4 pump ( Cousins et al., 2001 ; Ainsworth and Rogers, 2007 ). A more recent study showed that eCO 2 led to an 8.4% reduction in day respiration rate and a 16.2% reduction in dark respiration, as decreased leaf N and chlorophyll contents ( Sun et al., 2022 ).…”
Section: Securing Reproductive Success By Harnessing Co 2 ...mentioning
confidence: 99%
“…In fact, terrestrial plant respiration releases about 6 times more CO 2 to the atmosphere than the anthropogenic total from fossil fuel consumption, cement production, and land-use change (∼60 versus ∼10 gigatonnes CO 2 per year) ( NASEM 2019 ). Crop respiration can be reckoned to contribute around 8 gigatonnes of CO 2 to the terrestrial total annually ( Field et al 1998 ; Joshi et al 2023 ), making crop CO 2 emissions alone almost as high as anthropogenic emissions.…”
mentioning
confidence: 99%
“…Despite the cardinal metabolic and biogeochemical significance of plant respiration and the potential to increase crop yields by cutting respiratory CO 2 loss ( Amthor et al 2019 ; Garcia et al 2023 ; Joshi et al 2023 ), plant respiration has long had far less research attention than photosynthesis—a situation that has been justly called an “asymmetry in crop-focused academic research” ( Reynolds et al 2021 ). This asymmetry is readily apparent from a search of plant science journals for articles relating to photosynthesis or respiration over the past 70 yr ( Fig.…”
mentioning
confidence: 99%
“…Furthermore, we have published a Perspective article discussing the posibility of cutting respiratory CO 2 to sustain crop productivity and manage atmospheric carbon, 3 a Commentary article on a recent breakthrough in vertical farming, 4 and several Reviews, and other articles covering topics, such as modern forestry, 5 smart breeding, 6 carbon‐nitrogen interplay, 7 and selenium in modern agriculture 8…”
mentioning
confidence: 99%
“…Furthermore, we have published a Perspective article discussing the posibility of cutting respiratory CO 2 to sustain crop productivity and manage atmospheric carbon, 3 a Commentary article on a recent breakthrough in vertical farming, 4 and several Reviews, and other articles covering topics, such as modern forestry, 5 smart breeding, 6 carbon-nitrogen interplay, 7 and selenium in modern agriculture. 8 There are various article types for the authors to choose including Original Research articles that report on new scientific findings, Resource articles that provide useful resources or tools for agricultural research or practice, Review/Perspectives that provide an overview or analysis of a particular topic or field related to agriculture, Correspondence that respond to or comment on previously published articles, Commentary that presents the author's opinion or perspective on a particular issue related to agriculture, News and Views that report on recent developments or news related to agriculture, and Patent articles that report on new patents related to agricultural innovations.…”
mentioning
confidence: 99%